Fight, Flight, Freeze: The Impact of a Dyslexia Simulation on Preservice Teachers - Carolyn Carlson (The Advocate, 2024)
Teachers must have an understanding of dyslexia, including characteristics, assessments, and interventions, but also an understanding of the reactions the students may display when faced with these learning difficulties. In addition, teachers need to be aware of how their typical classroom practices may cause even further disruptions and challenges to the student rather than supporting them in their learning. This study asked preservice teachers to participate in the Experience Dyslexia simulation to gain new insight into not only the challenges faced by students with dyslexia regarding brain-based processing issues, but also how the classroom environment contributes to those difficulties. By completing the six stations and focusing on their personal reactions of fight, flight, or freeze, participants gained a deeper understanding of how they may see those similar types of responses in their students with dyslexia. Further, participants overwhelmingly indicated that experiencing this simulation will have an impact on their future teaching.
Keywords: dyslexia; simulation; literacy